Reporting of the Politika Belgrade daily newspaper on the epidemic of typhus in Serbia during the First World War - Barović, Vladimir; Dejan, Pralica; Ivanić, Ivana (Vojnosanitetski pregled, 2021)
Background/Aim. The epidemic of typhus lasted for several months in the Kingdom of Serbia during the First World War, and a vast number of people lost their lives. The objective of the paper was to investigate how the Politika, Belgrade daily newspaper, informed the then Serbian public about the epidemic of typhus in the Great War. Methods. By using statistical and historical-critical method, the analysis of all texts published in the Politika from February 1915, when the Serbian government and the Supreme Command allowed the press to write about the epidemic of typhus, until the outbreak began to calm down at the beginning of May 1915, was performed. Results. In the observed period, among the texts dedicated to the typhus epidemic, news about people who died of typhus (obituaries), news about the epidemic itself, as well as affirmative texts about the feats of doctors. There were more texts about allies’ military missions than about Serbian Army Medical Corps. The reporting was balanced and highly professional. Conclusion. In the period February–May 1915, a number of different articles about the typhus epidemic in Serbia during the Great War were published in the daily newspaper Politika. The reporting was well-balanced, ethical and highly professional.